PENGARUH CORPORATE SOCIAL RESPONSIBILITY LINGKUNGAN DAN SOSIAL TERHADAP KINERJA KEUANGAN PERUSAHAAN DENGAN TATA KELOLA CORPORATE SOCIAL RESPONSIBILITY SEBAGAI VARIABEL MEDIASI (Studi Empiris Seluruh Perusahaan Terdaftar di Bursa Efek Indonesia pada Tahun 2013-2016) - Kevin Dio Putrawieka; Imam Ghozali (Diponegoro Journal of Accounting, 2018)
This study aims to examine the mediating effects of the CSR governance performance in influencing the direct relationship between CSR environtemtally-oriented performance and CSR socially-oriented performance toward corporate financial performance. The independent variables in this research are CSR environtmentally-oriented performance and CSR socially-oriented performance. Mediation variable in this research is CSR governance performance. While the dependent variable used in this study is corporate financial performance.This study uses secondary data from financial statements of companies listed on the Indonesia Stock Exchange and Bloomberg database. The selected samples collected from all companies that publish its financial statements and present data on ESG CSR performance which consists of environmental, social, and governance reporting in 2013-2016 respectively and available in Bloomberg. This study uses multiple regression analysis, path analysis, and Sobel test to examine the relationship between independent variable, mediation variables, and dependent variable.The results showed that CSR environtmentally-oriented performance and CSR socially-oriented performance has a positive effect on the corporate financial performance. Furthermore, the mediation variable, CSR governance performance mediate the positive relationship between both variables independent and corporate financial performance.